Recent Developments of Metal and Metal Oxide Nanocatalysts in Organic Synthesis - A. Makawana, Jigar; B. Sangani, Chetan; Yao, Yong-Fang; Duan, Yong-Tao; Lv, Peng-Cheng; Zhu, Hai-Liang (Mini Reviews in Medicinal Chemistry, 2016)
Recently, various nanomaterials have been used in many organic transformations as efficient catalysts. The development of new catalysts by nanoscale design has emerged as a fertile field for research and innovation. The ability of nanotechnology to enhance catalytic activity opens the potential to replace expensive catalysts with lower amounts of inexpensive nanocatalysts. Besides, development of efficient and environmentally friendly synthetic methodologies for the synthesis of compound libraries of medicinal scaffolds is an attractive area of research in both academic and pharmaceutical industry. According to above reports and needs, this review deals with applications of nanoparticles as catalysts in various organic syntheses. We detail the topic of organic transformations using nanoparticles: Metal Nanoparticles and Metal Oxide Nanoparticles. In the latter part, different Metal Oxide Nanoparticles, such as ZnO Nanoparticle, TiO2 Nanoparticle, and CuO Nanoparticle are discussed.
Keywords: Metal Nanocatalysts